2010
DOI: 10.1097/mbc.0b013e328338dc49
|View full text |Cite
|
Sign up to set email alerts
|

Weight-adjusted dalteparin for prevention of vascular thromboembolism in advanced pancreatic cancer patients decreases serum tissue factor and serum-mediated induction of cancer cell invasion

Abstract: The aim of the present study was to assess the role of tissue factor and serum-induced cell invasion in patients with advanced pancreatic cancer (APC). A cohort of 39 patients with APC, without thrombosis, receiving chemotherapy, were entered in a randomized controlled trial (ISRCTN = 76464767) of thromboprevention with weight-adjusted dalteparin (WAD). A total of 19 patients received WAD, the remaining 20 acting as a control group. Serum from baseline and week 8 was analysed for circulating-tissue factor anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Although heparin exerts its anticoagulant activity primarily through allosteric modification of ATIII , there are a number of possible alternative mechanisms by which heparin may improve MSC deliverability. Possible inhibition of TF expression by heparin has been examined in pancreatic cancer patients, in whom heparin caused reduction in the levels of circulating TF . In cancer cell lines, heparin downregulates TF mRNA expression suggesting that culture of MSC with heparin may be considered to reduce potential adverse procoagulant activity ab initio.…”
Section: Discussionmentioning
confidence: 99%
“…Although heparin exerts its anticoagulant activity primarily through allosteric modification of ATIII , there are a number of possible alternative mechanisms by which heparin may improve MSC deliverability. Possible inhibition of TF expression by heparin has been examined in pancreatic cancer patients, in whom heparin caused reduction in the levels of circulating TF . In cancer cell lines, heparin downregulates TF mRNA expression suggesting that culture of MSC with heparin may be considered to reduce potential adverse procoagulant activity ab initio.…”
Section: Discussionmentioning
confidence: 99%
“…The exact contribution of TF‐MPs to the development of VTE may therefore be highly variable between tumor types, and the association with pancreatic cancer may reflect the high level of TF expression relative to other cancer types and/or the late stage of disease presentation . Somewhat surprisingly, however, whereas ~ 80% of pancreatic cancer patients show increased TF levels, < 30% of these patients are found to develop thrombosis , indicating that elevated TF‐MP levels in isolation do not unequivocally trigger thrombosis, and raising the interesting question of why the clinically recorded thrombosis rate is so much lower. Intriguingly, the occurrence of a thromboembolic event in these patients is often accompanied by the presence of persistent inflammation.…”
Section: The Contribution Of Tf To Cancer‐associated Thrombosismentioning
confidence: 99%
“…The potential anti-metastatic activity of heparin and LMWH that is independent of its antithrombotic effect is supported by data from many in vitro and in vivo studies [10][11][12][13][14][15][16][17][18][19][20][21]. Several clinical studies as well as meta-analyses have found significant improvement in 3-month and 6-month survival in cancer patients who are treated with LMWH compared to cancer patients treated with unfractionated heparin [9,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 96%